From Neanderthals to Homo sapiens: New palaeoecological and tephrocronological data from the MIS3 layers of Grotta-Riparo di Uluzzo C (Apulia, southern Italy) - Juan Ochando; Donatella Magri; Biagio Giaccio; Giovanni Zanchetta; Antonino Vazzana; Omry Barzilai; Francesco Berna; Gruppo Speleologico Neretino; Giulia Marciani; Andrea Zerboni; Sara Silvestrini; Enza E. Spinapolice; et al. (Quaternary Science Reviews, 2026)

Not just a technique! An experimental approach to refine the definition of the bipolar anvil reduction in the Uluzzian - Davide Delpiano; Giulia Marciani; Jacopo Conforti; Serena Lombardo; Matteo Rossini; Marcos César Pereira Santos; Stefano Benazzi; Marco Peresani; Adriana Moroni (Archaeological and Anthropological Sciences, 2024)

Late Neanderthal “menu” from northern to southern Italy: freshwater and terrestrial animal resources - Matteo Romandini; Sara Silvestrini; Cristina Real; Federico Lugli; Laura Tassoni; Lisa Carrera; Federica Badino; Eugenio Bortolini; Giulia Marciani; Davide Delpiano; Marcello Piperno; Carmine Collina; et al. (Quaternary Science Reviews, 2023)

Integrated multidisciplinary ecological analysis from the Uluzzian settlement at the Uluzzo C Rock Shelter, south‐eastern Italy - Sara Silvestrini; Matteo Romandini; Giulia Marciani; Simona Arrighi; Lisa Carrera; Andrea Fiorini; Juan Manuel López‐García; Federico Lugli; Filomena Ranaldo; Viviane Slon; Laura Tassoni; Owen Alexander Higgins; et al. (Journal of Quaternary Science, 2022)
The Middle to Upper Palaeolithic transition, between 50 000 and 40 000 years ago, is a period of important ecological and cultural changes. In this framework, the Rock Shelter of Uluzzo C (Apulia, southern Italy) represents an important site due to Late Mousterian and Uluzzian evidence preserved in its stratigraphic sequence. Here, we present the results of a multidisciplinary analysis performed on the materials collected between 2016 and 2018 from the Uluzzian stratigraphic units (SUs) 3, 15 and 17. The analysis involved lithic technology, use‐wear, zooarchaeology, ancient DNA of sediments and palaeoproteomics, completed by quartz single‐grain optically stimulated luminescence dating of the cave sediments. The lithic assemblage is characterized by a volumetric production and a debitage with no or little management of the convexities (by using the bipolar technique), with the objective to produce bladelets and flakelets. The zooarchaeological study found evidence of butchery activity and of the possible exploitation of marine resources, while drawing a picture of a patchy landscape, composed of open forests and dry open environments surrounding the shelter. Ancient mitochondrial DNA from two mammalian taxa were recovered from the sediments. Preliminary zooarchaeology by mass spectrometry results are consistent with ancient DNA and zooarchaeological taxonomic information, while further palaeoproteomics investigations are ongoing. Our new data from the re‐discovery of the Uluzzo C Rock Shelter represent an important contribution to better understand the meaning of the Uluzzian in the context of the Middle/Upper Palaeolithic transition in south‐eastern Italy.

Between the hammerstone and the anvil: bipolar knapping and other percussive activities in the late Mousterian and the Uluzzian of Grotta di Castelcivita (Italy) - Simona Arrighi; Giulia Marciani; Matteo Rossini; Marcos César Pereira Santos; Andrea Fiorini; Ivan Martini; Daniele Aureli; Federica Badino; Eugenio Bortolini; Carla Figus; Federico Lugli; Gregorio Oxilia; et al. (Archaeological and Anthropological Sciences, 2020)

Neanderthal occupation during the tephra fall-out: Technical and hunting behaviours, sedimentology and settlement patterns in SU 14 of Oscurusciuto rock shelter (Ginosa, southern Italy) - Giulia Marciani; Vincenzo Spagnolo; Ivan Martini; Alessio Casagli; Roberto Sulpizio; Daniele Aureli; Paolo Boscato; Annamaria Ronchitelli; Francesco Boschin (Archaeological and Anthropological Sciences, 2020)

Backdating systematic shell ornament making in Europe to 45,000 years ago - Simona Arrighi; Eugenio Bortolini; Laura Tassoni; Andrea Benocci; Giuseppe Manganelli; Vincenzo Spagnolo; Luca Maria Foresi; Anna Maria Bambini; Federico Lugli; Federica Badino; Daniele Aureli; Francesco Boschin; et al. (Archaeological and Anthropological Sciences, 2020)

Climbing the time to see Neanderthal behaviour’s continuity and discontinuity: SU 11 of the Oscurusciuto Rockshelter (Ginosa, Southern Italy) - Vincenzo Spagnolo; Giulia Marciani; Daniele Aureli; Ivan Martini; Paolo Boscato; Francesco Boschin; Annamaria Ronchitelli (Archaeological and Anthropological Sciences, 2020)